Figure of General Olexander Grekov in historiography of independent Ukraine - Nataliia Panas (Cхід)
The article presents a complex of scientific work for studying the military-political activity of General A. Grekov, outlines the main problems that a researcher will encounter in the analysis of the general's figure, identifies the features and tendency of historiographic research in the field of military biography of the period of independent Ukraine. The scientific value of each source is analyzed and a brief description of the thematic works is given. The historiography of the period of independent Ukraine has an inherent desire to make up for the gaps of its development in the period of the USSR. Many scientific works are published on the professional activity of the senior military leadership during the National Liberation Competitions of 1917-1921. Despite the continuing study of military construction issues during the revolution, the personnel potential of the Armed Forces, many issues remain poorly understood, or even not at all. Аccordingly General Olexander Grekov's name is largely mentioned by historians in the context of the historical events in which he participated directly, without creating a separate holistic study. The pioneer in the study of the life path of the General was Yaroslav Tynchenko. Subsequently, he was joined by Mykhailo Kovalchuk and Olexander Diedyk, who, although not comprehensively investigated the military-political activities of the general, but in their works made considerable efforts to present his achievements during the Ukrainian Revolution. Most of electronic resources selectively describe O. Grekov's life, are of a popular science character, and are aimed at an unprepared reader. Individual works also do not exhaust the problem, since they are biographical directories or collections of essays, therefore limited in scope, do not cover the full life and activities of the general. Thus, there is an urgent need to create a separate special study on these topics, which will help to shape the military doctrine of an independent Ukraine and help to fully and objectively reproduce the picture of the events of a hundred years ago.